(untitled) (Advances in Civil and Architectural Engineering, 2021)
Experimental tests demonstrated the importance of the axial load variation in the seismic response of RC columns, namely, through the reduction in the strength capacity, reduced deformation capacity, and reduced energy dissipation capacity. Thus, this manuscript aims to study the axial load variability of RC columns, according to the plan and height disposition, and assess the relationship between the corresponding column flexure capacity and its influence on the global response of the structure. Hence, three RC structures were modeled using the software SeismoStruct and subjected to non-linear static pushover and dynamic analyses. According to the results, which are assessed in terms of capacity curves, axial load variation, and story/global shear capacity of each model, it can be concluded that the axial load variation is higher in the bottom storys and decreases with the story height of the structure. As observed, the corner columns reached a higher axial load variation than the façade and central columns.